ENVIRONMENTAL CONSTITUTIONAL REGRESSION IN RISK-BASED INVESTMENT GOVERNANCE: RECONFIGURING ENVIRONMENTAL PROTECTION STRUCTURE IN INDONESIA - Amir, Irfan; Setyawanta, Lazarus Tri; Diamantina, Amalia; Ansar, Lukman; Adelvia, Adelvia (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
The reform of the risk-based licensing system implemented through the Job Creation Law in Indonesia has had a significant impact on environmental protection. This shift, which replaces the precautionary-based preventive approach with risk management, has the potential to reduce ecological protection without explicitly changing constitutional norms. From a constitutional perspective, this change is considered environmental constitutional regression, referring to the decline in the legal system’s ability to ensure the environmental protection that was previously achieved. This article analyzes the impact of this transformation on the legal structure and investment governance in Indonesia. Environmental protection, which previously functioned as a constitutional instrument limiting the rationality of economic development, is now repositioned as an administrative component within the risk-based licensing framework. This shift occurs amid efforts to deregulate and simplify licensing to accelerate investment, but at the expense of the state’s obligation to ensure ecological sustainability. This reform affects various regulatory dimensions, including institutional structure, the role of law, public participation procedures, and environmental protection standards. The integration of environmental approval into the risk-based licensing system changes the paradigm from preventive control to administrative risk management. As a result, environmental protection mechanisms become dependent on risk assessments that do not always encompass the broader potential ecological damage. This study proposes the need for a progressive legal approach that reaffirms the state's obligation to uphold constitutional rights to a healthy and sustainable environment, while mitigating the negative impacts of regulatory reform on ecological justice and environmental sustainability. Thus, this research contributes to the understanding of the constitutional implications of risk-based regulatory restructuring, emphasizing the importance of ensuring that environmental protection remains a priority in development policy.